Causative Microorganisms and Antibiotics Susceptibility in Neonatal Sepsis at Neonatal Intensive Care Unit: A Longitudinal Study from Diyala Governorate in Iraq - Issam Tariq Abdul Wahaab1 , Sura Qais Mahmood Almaroof 2, Zaid Taha Yaseen3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Neonatal sepsis is classified into two types, early-onset and late-onset sepsis, depending onthe time of appearance of the clinical features of neonatal sepsis.Objective: We aim to detect the most common causative organisms of neonatal sepsis and to evaluate thecorresponding antibiotics susceptibility in the Diyala governorate.Patients and Methods: We prospectively collected a convenient sample of 106 sepsis-proven neonatesfrom the neonatal intensive care unit at Al-Batool teaching hospital. We assessed all cases based on clinicalfeatures, laboratory investigations, and demographics.Results: Late-onset neonatal sepsis was predominant (77.4%) among neonates, and it was significantlyassociated with neonatal prematurity and the mode of delivery at p-values of 0.03 and 0.045 respectively.Premature neonates and those who were the product of cesarean section were more prone to developlate-onset neonatal sepsis with a relative risk of 2.8 and 2.54 respectively. The most common causativemicroorganism of early-onset neonatal sepsis was found to be Escherichia coli in 45.8% of cases whilethose causing late-onset neonatal sepsis were mainly due to Gram-negative bacilli represented by Klebsiellapneumonia (46.3%) and Acinetobacter baumannii (24.4%). Multi-drug resistance was evident for most ofthe causative microorganisms.Conclusion: To recapitulate, late-onset sepsis appeared was more common among Iraqi neonates, and it wassignificantly associated with the neonate prematurity and C-section mode of delivery.